Fungicidal activities of Cymbopogon winterianus against anthracnose of banana caused by Colletotrichum musae - Mark Anthony Angeles Mangoba; Dionisio de Guzman Alvindia (Scientific Reports, 2023)
Abstract The genus Cymbopogon (Poaceae) species have been widely cultivated throughout the world for a wide range of uses in the pharmaceutical and agricultural fields. The current work investigates the fungicidal activities of Cymbopogon winterianus extract (CWE) in controlling the C. musae that caused anthracnose disease in banana fruit. In vitro assay results showed that CWE at 1.5–2.5 gL−1 concentrations controlled the development of the test pathogen. Mycelial blast, cytoplasmic discharge, and spore edema were noticed when CWE was applied. The Minimum Effective Concentration (MEC) of CWE for the in vivo assay was 1.50 gL−1 and can be used as a postharvest treatment on banana fruit to deter anthracnose infection. Moreover, no visible phytotoxicity or changes in aroma were observed on banana fruit treated with CWE, even at the highest concentration of 2.5 gL−1. The GCMS analysis revealed 41 chemical components associated with CWE. The five main compounds were the following: Methyl oleyl ether (40.20%), γ-Sitosterol (15.80%), 6-Methylheptan-3-ol (7.13%), α-Terpineol (5.56%), and n-Pentadecanol (4.05%). The CWE possesses excellent fungicidal effects against C. musae; in the near future, it can be used as an alternative to commercially available traditional fungicides on the market.